2021
DOI: 10.1063/5.0070275
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature electroluminescence properties of InGaN red 40 × 40 μ m2 micro-light-emitting diodes with a peak external quantum efficiency of 3.2%

Abstract: We study the high-temperature electroluminescence properties of 600 nm InGaN red 40 × 40 μm2 micro-light-emitting diodes (μLEDs) with a peak external quantum efficiency (EQE) of 3.2%. Temperature-dependent peak wavelength measurements show a low redshift of 0.05 nm/K. The injection efficiency improves with increasing temperature. The hot/cold (HC) factor is used to quantify the thermal droop: at 400 K, the EQE and wall-plug efficiency HC factors at 50 A/cm2 reach high values of 0.72 and 0.85, respectively. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
1
26
1
1
Order By: Relevance
“…In 2021, Li et al from UCSB demonstrated significant progress of InGaN red µLEDs on PSS [5][6][7]. As discussed in Section 2.1, the packaged 607 nm InGaN red µLEDs show a peak EQE of 2.4% to 2.6% as the size reduces from 100 × 100 µm 2 to 20 × 20 µm 2 .…”
Section: Robust Temperature Property Of Ingan Red µLedsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2021, Li et al from UCSB demonstrated significant progress of InGaN red µLEDs on PSS [5][6][7]. As discussed in Section 2.1, the packaged 607 nm InGaN red µLEDs show a peak EQE of 2.4% to 2.6% as the size reduces from 100 × 100 µm 2 to 20 × 20 µm 2 .…”
Section: Robust Temperature Property Of Ingan Red µLedsmentioning
confidence: 99%
“…In contrast, InGaN red µLEDs show a robust thermal property. P. Li et al from UCSB investigated the high-temperature EL properties from 300 K to 400 K of InGaN red µLEDs (40 × 40 µm 2 ) [7,14]. The 600 nm InGaN red µLEDs show a high peak EQE of 3.2%.…”
Section: Robust Temperature Property Of Ingan Red µLedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, InGaN/GaN multi-quantum-well materials and structures have been intensively studied and identified as an emerging platform for constructing wavelength-tunable LEDs due to their continuously variable bandgap ranging from 0.7 to 3.4 eV. [1][2][3][4][5][6] Particularly, display technology based on micro-and nano-sized LEDs has attracted significant attention for comprehensive applications, including ultrahigh resolution lighting and displays, biomedical imaging, augmented/virtual reality, sensing, etc. For nearly two decades, painstaking efforts have been carried out to shrink the areal sizes of traditional InGaNbased materials, structures and devices.…”
Section: Introductionmentioning
confidence: 99%